STEM outreach program of Smart Control Helicopter competition in Malaysia: a descriptive analysis - Sabirin Abdullah,; Roslinda Rosli,; Gan, Kok Beng; Mardina Abdullah,; Lilia Halim,; Norisza Dalila Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The objective of the paper is to present findings of a Science Technology Engineering and Mathematics (STEM) outreach program on Smart Control Helicopter. The program involved 27 school students in Selangor, Malaysia where they learned a microcontroller board called Arduino to control mini helicopters. Students had exposed to the procedures to assemble simple circuits for the control system, the connection process of the circuit to a microcontroller, and communication with the computer. The activity has equipped the students with basic knowledge in performing accurate programming to maneuver a mini helicopter. A few university students assisted the learning activities based on a developed module. The program was conducted in the form of a competition to self-motivate the students. The students completed a questionnaire and quiz on the technical knowledge of technology and electronics. As a result, students were able to gain knowledge on the related skills and showed active participation during the hands-on activities.